PERILAKU BRAND SWITCHING PENGGUNA TELEPON SELULER SMARTFREN - Tafiprios .; Rina Astini (Universitas Mercu Buana, 2019)
The purpose of this study was to determine the effect of consumer dissatisfaction, needs to seek variations, and product quality on brand switching behavior from Smartfren mobile phones to other mobile brands. A total of 140 respondents who had used smartfren mobile phones and then switched brands to other cellphones were used in this study. Data collected through questionnaires using a Likert scale. Analysis of this research data using SEM with Lisrel 8.8. The results showed that consumer dissatisfaction did not have a significant effect on brand switching behavior, while the need to seek variation and product quality had a significant effect on brand switching behavior